Correlation Analysis of Refractive and Visual Quality after Wavefront-Optimized Laser In Situ Keratomileusis for 50% and 100% Angle Kappa Compensation. (5th October 2020) - Ru, Xin-Yu; Li, Zheng-Ri; Li, Cheng-Lin; Cui, Hong; Deng, Wen-Qing; Lin, Shu-Hua; Jia, Yu-Jie; Li, Ying-Jun
Abstract : Purpose . To analyze the distribution of the offset between the pupil center and the coaxially sighted corneal light reflex ( P-Dist ), the effects of 50% and 100% angle kappa adjustments on refractive and visual quality in patients with moderate myopia were investigated. Methods . A randomly selected 254 patients (254 eyes) with moderate myopia who underwent femtosecond laser-combined LASIK were examined. During the operation, the P-Dist of the patients was recorded by the x- and y-axis eyeball-tracking adjustment program of the WaveLight Eagle Vision EX500 excimer laser system. Preoperatively and 3 months postoperatively, the WaveLight® ALLEGRO Topolyzer was used to measure the pupil size and center position, and the wavefront sensor was used to measure the wavefront aberrations. The visual function tester (OPTEC 6500) measured contrast sensitivity. Results . The average P-Dist was 0.220 ± 0.102 mm. When the P-Dist >0.220 mm, the postoperative residual cylinder was 0.29 ± 0.34 D in the group with the 50% adjustment and 0.40 ± 0.32 D in the 100% group, which was significantly higher than the 50% group P = 0.036 . The coma was 0.21 ± 0.17 μ m in the 50% adjusted group and 0.34 ± 0.25 μ m in the 100% group, which was significantly higher than that in the 50% group P = 0.021 . At the 1.5 c/d spatial frequency, contrast sensitivity in the adjusted 100% group was significantly lower than that in the 50% group under visual glare conditions P = 0.039 . Conclusion . The postoperative visual acuity and spherical equivalent were not affected in the two groups. However, when P-Dis t >0.220 mm, the residual astigmatism and coma were lower in the 50% group. Individualized operations for those with moderate myopia and large-angle kappa in which 100% adjustment is chosen may not result in a better visual quality effect than 50%.